Pengaruh Fasilitas dan Kualitas Pelayanan Terhadap Tingkat Kepuasan Pelanggan pada Salon Kecantikan di Kecamatan Talawi Kota Sawahlunto - Sandya Putri Delvita; Rahmi Oktarina (Pusat Riset dan Inovasi Nasional, 2024)
The background of this research focuses on the development of the beauty salon industry which is getting heavier. Beauty salons offer a variety of services aimed at improving the appearance. Beauty salons must understand the factors that affect customer satisfaction. This study aims to analyze the influence of facilities and service quality on the level of customer satisfaction in beauty salons in Talawi District, Sawahlunto City. This research is a type of causal associative research using a quantitative approach. The data collection technique used in this study is to distribute a questionnaire through a g-form that has been tested for validity and reliability to 82 respondents as a research sample. . The data collected includes personal information of salon respondents regarding the facilities provided and the quality of services received. The results of the study show that facilities and service quality significantly affect customer satisfaction. The results of the hypothesis test showed that the three hypotheses proposed were accepted. The Adjusted R Square value of 0.745 shows that 74.5% of the variation in customer satisfaction can be explained by facilities and service quality, while 25.5% can be explained by other variables outside this study. Therefore, it is important for beauty salons to improve facilities and service quality to increase customer satisfaction in order to meet customer expectations and increase their loyalty to the salon.